Study on Hot Press Forming Die Condition by using Vibration Monitoring System - Chuan Huat, Ng; Suhaimi, Adam Arif (Research Progress in Mechanical and Manufacturing Engineering, 2020)
Hot Press Forming (HPF) was one of the most important forming processes in vehicle manufacture industries. In producing lightweight automotive, sheet metal forming was one of the essential manufacturing processes in producing vehicular parts. However, delayed fault detection was the issue that leads to great loss for industry. To resolve the problem, Tool Condition Monitoring System (TCMS) was implemented in manufacturing operation. In this case study, the sheet metal forming and vibration monitoring as a system health monitoring of the process were studied. The case study consists of different vibration sensors used in condition monitoring of the health of the machines. During hot press forming, the blank deformation produced vibration wave, which then received by vibration sensor that would be attached on stamping die wall. Then the vibration data signal results obtained by DAQ as a data acquisition system was viewed in time-domain analysis and frequency-domain analysis. The pattern and characteristic of amplitude in frequency domain graph obtained by accelerometer sensor was then analyzed and related with other types of sensors used in the case studies. The mount position of each types of sensors were also reviewed and compared and then, the best mount position of the sensor was then developed. All the case studies reviewed in this thesis had the same method of signal conditioning of the vibration signal wave. From this project study, the signal amplitude in stamping die of the normal conditioned machines were compared to the defected conditioned machines. Both average and peak amplitude were influenced by surface roughness and clearance of stamping die and punch. At the end of project, the correlation of stamping die condition with others factor in manufacturing process will be determined through recommended system health monitoring.